Development and Experimental Research on CO2 Transcritical Expander (Zhileng xuebao)
As a natural working fluid, CO 2 is receiving more and more attention in the refrigeration. The key technology of the research of CO 2 transcritcia cycle is to improve the coefficient of performance of the system that is competitive with present conventional high performance refrigerant systems. In order to lower the throttling losses in the CO 2 transcritical cycle, the significant measure is to replace the throttling valve by an expander. This paper presents the development of the rolling piston expander and the activity items in the expander design, including the seal technology, the contact friction control and suction design. The experiments of the CO 2 expander conducted in our CO 2 transcritical cycle rig are described. The results show that the power output of the expander is related to the loads of the generator. The measured efficiency of this prototype is up to 32% and the further improvement of the expander is required.